From protection to pollution: Evaluating environmental and human health risks of acaricide use in dairy farming in Kenya - Maina, Kevin W.; Parlasca, M.C.; Rao, E.J.O. (2025)
Sustainable intensification of livestock production relies critically on effective disease management, yet the environmental implications of current practices remain poorly understood. The study was designed to evaluate the efficacy of acaricide use in tick control in Kenya’s dairy sector affects environmental and human health risks. Using original survey data from dairy farmers and a two-stage least square (2SLS) approach, the results found that farmers’ adaptation to perceived ineffective tick treatment leads to potentially harmful practices. Twenty percent of farmers improperly rotate acaricides, while 66% under-apply recommended doses. Despite 65% using protective gear, 29% report adverse health effects. Our estimates show that improper acaricide group rotation increases the environmental and human health risks by 35%. The study highlights important trade-offs between animal health management and environmental and human health objectives, suggesting a need to reform current disease prevention approaches to balance productivity gains with environmental sustainability in developing countries.